2006
DOI: 10.1152/ajpgi.00386.2005
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid transport and metabolism in HepG2 cells

Abstract: The mechanism(s) of fatty acid uptake by liver cells is not fully understood. We applied new approaches to address long-standing controversies of fatty acid uptake and to distinguish diffusion and protein-based mechanisms. Using HepG2 cells containing an entrapped pH-sensing fluorescence dye, we showed that the addition of oleate (unbound or bound to cyclodextrin) to the external buffer caused a rapid (seconds) and dose-dependent decrease in intracellular pH (pH(in)), indicating diffusion of fatty acids across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 51 publications
5
45
1
1
Order By: Relevance
“…The enhanced oleate uptake was not accompanied by an accumulation of free oleate in the cells. Only 5-8% of oleate remained unesterified, which is in line with other reports (Guo et al, 2005;Pohl et al, 2002;Stremmel and Berk, 1986).…”
Section: Analysis Of Fatty Acid Uptakesupporting
confidence: 93%
“…The enhanced oleate uptake was not accompanied by an accumulation of free oleate in the cells. Only 5-8% of oleate remained unesterified, which is in line with other reports (Guo et al, 2005;Pohl et al, 2002;Stremmel and Berk, 1986).…”
Section: Analysis Of Fatty Acid Uptakesupporting
confidence: 93%
“…We demonstrated in both cell types that adsorption and transbilayer movement of OA delivered by MBCD are complete within seconds and that all of the OA that had been complexed with MBCD partitioned from MBCD into the cell membrane. We also showed that MBCD did not affect the recovery of BCECF fl uorescence in HepG2 cells, which closely follows FA metabolism (mainly FA esterifi cation) ( 25,37 ). Therefore, MBCD can deliver FA to cells without altering the plasma membrane structure and FA metabolism.…”
Section: Mbcd Delivers Fa To Cells Rapidly and Does Not Interfere Witmentioning
confidence: 72%
“…These cells metabolize FA faster than 3T3-L1 preadipocytes, which is detected as recovery in the BCECF fl uorescence ( 25 ). As shown in Fig.…”
Section: Conditions For Preparation Of Mbcd Complexes With Famentioning
confidence: 78%
See 1 more Smart Citation
“…There are two main pathways by which LA may affect the cells: (1) etherification into phospholipids to influence the membrane fluidity, and (2) providing energy for cell cycle, while a part of LAs would be transferred into 9/13-hydroxyoctadecadienoic acid (9/13-HODE) by the action of 15-lipoxygenase (15-LOX) enzyme, and become elongated and desaturated into long chain PUFAs by the action of elongases and desaturases (Kelavkar et al, 2006a;2006b;Guo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%